1999
DOI: 10.1149/1.1391749
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde Gas‐Sensing Properties and Surface Chemistry of SnO2 ‐ Based Sensor Materials

Abstract: Acetaldehyde gas‐sensing properties of SnO2 , loaded with and without a noble metal, were investigated, and the results are discussed in terms of the level of sensor resistance in air and oxidation behavior of acetaldehyde over sensor materials. Of the noble metals tested, Rh was found to be the best sensitizer, and the highest sensitivity was achieved with SnO2 loaded with 0.1 wt % Rh at 350°C. The sensitivity enhancement is explained by the increased sensor resistance in air due to the electronic interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…According to our estimations, 1.0 ML corresponded to the averaged thickness of the rhodium coverage ~ 0.3 nm . However, numerous studies have shown that such coatings are not optimal for many applications, including catalysis and gas sensorics . The optimum characteristics of the sensors and catalysts were obtained at much lower rhodium concentrations on the surface of the metal oxides.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…According to our estimations, 1.0 ML corresponded to the averaged thickness of the rhodium coverage ~ 0.3 nm . However, numerous studies have shown that such coatings are not optimal for many applications, including catalysis and gas sensorics . The optimum characteristics of the sensors and catalysts were obtained at much lower rhodium concentrations on the surface of the metal oxides.…”
Section: Introductionmentioning
confidence: 77%
“…The optimum characteristics of the sensors and catalysts were obtained at much lower rhodium concentrations on the surface of the metal oxides. For example, Shimizu et al believe that the optimum gas sensitivity effect was achieved at the rhodium concentration of 0.1 wt%. According to Vis et al, the hydrogen chemisorption on the Rh/TiO 2 catalyst, [H]/[Rh], also strongly increased with a decrease in metal loading below 0.5 wt%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity, selectivity stability of the device is dependent on many other factors. Nanostructures of ZnO, SnO 2 grown by different methods have been studied to increase the response time, stability sensitivity of the sensor to aldehydes [12][13][14][15]. Metal oxides such as SnO 2 , In 2 O 3 , combination of oxides such as WO 3 -Sb 2 O 4 , SnO 2 -In 2 O 3 -CdO have been studied for formaldehyde sensing [11,16].…”
Section: Various Sensors For Aldehyde Detectionmentioning
confidence: 99%